General didactic and specific principles of work in computer-oriented learning environments (Pedagogy of Higher and Secondary Education, 2012)
Tverezovska N. T., Kasatkin D. YU. General didactic and specific principles of work in computer-oriented learning environments.The features of student learning in computer-oriented learning environments are defined; general didaktic and specific principles of operation, the characteristics inherent in computer-oriented learning environments are given.
Keywords: learning environment; principles; distance education; information and communication technology